Management concepts for the sustainable development of mineral resources - S. S. Salmanov; Z. M. Nazarova; Yu. A. Leonidova (Известия высших учебных заведений: Геология и разведка)
Background. The development and implementation of the life cycle concepts of extracted raw materials seems promising for the sustainable development of mineral resources by a mining company. The practical implementation of such concepts requires a system of theoretical, methodological, analytical, and organizational procedures developed in close collaboration by state officials, researchers, and subsoil users with a particular focus on the responsibility of producers.Aim. To carry out an analysis of the existing theoretical concepts for managing the mineral resource base of mining companies and to assess their implementation prospects. The following objectives were formulated: 1) to analyze the current situation in the field of reproduction of mineral resources; 2) to review the management approaches currently used to reproduce mineral resources; 3) to evaluate the prospects of modern concepts for the management of mineral resources in the mining industry.Materials and methods of research. The authors analyzed the publications of foreign and domestic authors in the field of sustainable development. The complex of studies included an analysis of the theoretical concepts of management of reproduction of the mineral resource base developed to date, grouping of key indicators for assessing the sustainability of a mining enterprise, comparing approaches to management of reproduction of the mineral resource base and others.Results. Specific features of the mechanistic approach to the management of mineral resources, as well as its limitations and drawbacks, were analyzed. Particular attention was paid to a concept of the life cycle of a mining plant. The possibilities and prospects of using a methodology of mineral resource capacity management are described.Conclusions. The transition to modern concepts in the management of mining enterprises can be achieved under the condition of changing the existing orientation to super-profitable gross mining to that balancing social, environmental, and economic considerations.